Alpha-Transfer Reaction technique for nuclear magnetic moment measurements (2019)
In this work the α-transfer reactions mechanism is studied as a technique to populate medium-tolow spin states in nuclei that cannot be produced with enough intensity in the present radioactive beam facilities. Uses of the α-transfer population mechanism to measure g factor and lifetimes, with the Transient Field Technique and the Doppler Shift Attenuation Method respectively, are presented. Some aspects of the theoretical model to approach the understanding of the mechanism, such as the Distorted Wave Born Approximation in combination with Optical Potentials, are also presented. Experimental challenges for future uses of the α-transfer technique are shown, and possible experimental campaigns are proposed with all possible combinations of stable beams that can populate radioactive nuclei. As part of this work an experiment using the reaction 28 14Si + 12 6 C −→ +32 16S + 4He + 4He was approved by the Program Advisor Committee at University of Sao Paulo, and will be carry out during 2019. A segmented γ-Ray detector LYSO(Ce) with an array of 16 ∆E-E particle detectors will be part of the detection system. In future experiments, it is expected to obtain a set of more detailed nuclear structure parameters to unveil the structure of the populated states.